STRUKTUR DAN MEKANISME TATA KELOLAH LEMBAGA KEROHANIAN - Oktavianus Pasoloran; Oktavianus Pasoloran; Fransiskus Randa (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2022)
This study discusses the implementation of spiritual institution) in the Conference Area Adventist spritual institutionorganization and the practice of financial reporting of Adventist spritual institutionorganizations in accordance with the principles of good governance. This research is a qualitative research where the primary data is obtained from the results of interviews with the leadership of the Seventh-day Adventist Spritual institutionorganization in the Conference Area. While secondary data is additional data. The results show that first, the mechanism for implementing Spiritual institutionin the Conference Area Adventist Spritual institutionorganization through the Conference Area Executive Committee (EXCOM) as the board of directors, the Finance Committee as the committee that evaluates financial reports and audit results of the congregation and conference area financial statements, internal auditors are carried out by the spritual institutionauditors and the General Conference Auditing Service (GCAS). The results of this study indicate that the Conference Area Adventist spritual institutionorganization has good management governance. Several improvements can be made by establishing a more independent audit committee and optimizing the work of the internal auditors. Second, in general, the practice of financial reporting in the working environment of the spiritual institution in the Conference Area is in accordance with the principles of good governance, namely transparency, accountability, responsibility, independence and fairness. Improvements need to be made to the communication media to the congregations so that financial supervision and management are more efficient, effective, economical, and productive (E3P).